Introducing sociology, using the stuff of everyday life - Johnston, Josée 1972-; Cairns, Kate; Baumann, Shyon 1971- (New York Routledge, Taylor & Francis Group, 2017)
"This comparatively concise, highly visual, and affordable book offers a refreshingly new way forward to reach students, using one of the most powerful tools in a sociologist's teaching arsenal-the familiar stuff in students' eveerday lives throughout the world: the jeans they wear to class, the coffee they drink each morning, or the phones their professors tell them to put away during lectures" -- Provided by publisher.
Part I. Surviving (and thriving) in consumer culture -- Part II. Fitting in: being part of the group -- Part III. Standing out: individuals negotiating the social world.
Includes bibliographical references (pages 425-454) and index.
Keywords: Sociology; Technological innovations -- Social aspects; Self -- Social aspects